Staffing the International Civil Service: The Influence of Nationality in Recruitments to the League of Nations Secretary, 1922-1930 - Nedergaard, Jacob (Culture and History: Student Research Papers, 2023)
This article examines how nationality influenced recruitment of the highest-ranking officials to three of the smaller, political sections in the League of Nations Secretariat during the organization’s most successful years between 1922 and 1930. From three, separate case-studies, it is shown that although the official policies favored the hiring of nationals from underrepresented member states, other factors such as the individual section’s autonomy and policy field further complicated the process of finding the right nationals for vacant positions. This meant that the established protocols for recruitment were oftentimes ignored or circumvented in attempts to guarantee the most suitable candidates.